Sm-Nd isochron age of the calcite from shewushan carlin-type gold deposit in the middle-lower yangtze metallogenic belt, eastern China - Lin, Dongyong; Xu, Rongke; Chen, Xin; Cai, Pengjie; Zheng, Shunli; Yu, Junzhen; Liu, Jia; Du, Wenyang; Wang, Minfang; Xu, Xingying (Frontiers in Earth Science, 2025)
The Shewushan gold deposit, situated in the western extension of Edongnan, marks the westernmost point of the Middle-Lower Yangtze Metallogenic Belt, is an important iron and copper mineralization area in the Middle-Lower Yangtze Metallogenic Belt (MLYB). Previous studies identified the Shewushan gold deposit as a Carlin-type gold ore, but its age remains controversial. This paper examines a set of widely distributed calcite veins in the Shewushan gold deposit. In hydrothermally altered carbonate rocks, calcite is texturally associated with ore-stage jasperoid and disseminated Au-bearing arsenian pyrite, suggesting synmineralization. Calcite veins concurrent with As- and Sb-sulfide mineralization are relatively enriched in middle rare earth elements and heavy rare earth elements. They yield Sm-Nd isochron age of 99.1 ± 2.4 Ma, with similar initial εNd values, ranging from −12.2 to −12.6. These ages are interpreted to record the age of decarbonation and gold deposition of the Carlin-type gold deposits in the MLYB, formed during the late stages of the Yanshanian Orogeny. This interpretation matches the Cretaceous Sporo-pollen fossil assemblages found in the Shewushan gold deposit in red laterite, siliceous rock, and limestone. This provides the first micropaleontological evidence showing that convecting meteoric water played an important role in mineralization. Late Cretaceous Carlin-type gold mineralization further supports the conclusion that late-stage copper-gold mineralization in the MLYB occurred more likely between ∼110 and 100 Ma, rather than ∼123–105 Ma. It also supports that ore-forming events in the MLYB were possibly contemporaneous with other parts of Eastern China and were also controlled by the drifting direction of the subducting Pacific plate. The tectonic and mineralization evolution during the Jurassic-cretaceous in the MLYB happened during the latest Cretaceous to early Tertiary. This indicates that the western extended part of Edongnan is not only a promising Carlin-type gold area, but also a potential target area for Cu–Mo–Au porphyry deposits, W–Cu–Au skarn deposits, Ag–Pb–Cu bearing veins, and epithermal Ag–Au deposits.